Learning technology for Ayurveda with pedagogically designed virtual patient case simulations - Prema Nedungadi; Prema Nedungadi; Rammanohar Puthiyedath; Romita Jinachandran; Shyamasundaran Kulangara; Sushma Naranappa Salethoor; Mandip Goyal; Nagarajan Chockan; Anup Thakur; Raghu Raman; Raghu Raman (Frontiers in Medicine)
IntroductionAyurveda education in India has seen limited integration of learning technology, leading to significant gaps in clinical skill development. This study introduces AyurSIM, a virtual patient simulation platform designed with interactive virtual cases replicating real-world scenarios to address this gap, offering structured educational modules from patient examination through follow-up care, incorporating Ayurveda protocols and a comprehensive database of disease patterns.MethodsAyurSIM was developed using pedagogical frameworks building on experiential learning, problem-solving tasks, and reflective practice. The platform enables the creation of regionally adapted virtual cases, aligning with diverse Ayurvedic practices while maintaining a structured protocol. Usability was evaluated using the validated System Usability Scale (SUS) among 210 diverse participants during training workshops.ResultsThe platform achieved a “good” SUS score of 77.08. Participants commended the intuitive interface, immersive learning experience, and educational value. Suggested improvements included integrating AR/VR technologies, expanding clinical content across disciplines, and multilingual support.DiscussionAyurSIM effectively bridges traditional Ayurveda education with modern methodologies, providing culturally responsive, practical learning experiences. The findings suggest that the blended pedagogical approach provides a robust framework for Ayurveda education. The ability to simulate realistic virtual patient clinical scenarios in a structured manner underscores the platform’s value in preparing students for real-world practice.